Implementasi Akad Murabahah pada Tepat Pembiayaan Syariah Kelompok Berdasarkan Kesesuaian PSAK 102 di BTPN Syariah Area IV Jurai Pesisir Selatan - Hafizah Hafizah; Murniati Murniati (CV. ITTC INDONESIA, 2024)
Bank BTPN Syariah is a sharia financial institution in the aspect of sharia banking and operates with Islamic sharia principles, with one of the Murabahah financing transactions and is very popular in the Exact Group Sharia Financing product. This research aims to find out how PSAK 102 is implemented and analyze the suitability of the murabahah contract treatment at Bank BTPN Syariah with PSAK 102. This research uses qualitative methods with a descriptive approach, namely by describing the implementation of the murabahah financing program at Bank BTPN Syariah IV Jurai, analyzing the suitability of accounting treatment on the recognition, measurement, presentation and disclosure of Murabahah financing at Bank BTPN Syariah IV Jurai with PSAK 102 through interviews, observation and documentation. The results of this research indicate that the Murabahah accounting treatment at Bank BTPN Syariah is not fully in accordance with the Murabahah accounting treatment in PSAK 102 which includes recognition and measurement of murabahah. Meanwhile, presentation and disclosure are in accordance with PSAK 102.